Clinical Profile, Arrhythmias, and Adverse Cardiac Outcomes in Emery–Dreifuss Muscular Dystrophies: A Systematic Review of the Literature - Anna Chiara Valenti; Alessandro Albini; Jacopo Francesco Imberti; Marco Vitolo; Niccolò Bonini; Giovanna Lattanzi; Renate B. Schnabel; Giuseppe Boriani (Biology, 2022)
Cardiolaminopathies are a heterogeneous group of disorders which are due to mutations in the genes encoding for nuclear lamins or their binding proteins. The whole spectrum of cardiac manifestations encompasses atrial arrhythmias, conduction disturbances, progressive systolic dysfunction, and malignant ventricular arrhythmias. Despite the prognostic significance of cardiac involvement in this setting, the current recommendations lack strong evidence. The aim of our work was to systematically review the current data on the main cardiovascular outcomes in cardiolaminopathies. We searched PubMed/Embase for studies focusing on cardiovascular outcomes in LMNA mutation carriers (atrial arrhythmias, ventricular arrhythmias, sudden cardiac death, conduction disturbances, thromboembolic events, systolic dysfunction, heart transplantation, and all-cause and cardiovascular mortality). In total, 11 studies were included (1070 patients, mean age between 26–45 years, with follow-up periods ranging from 2.5 years up to 45 ± 12). When available, data on the EMD-mutated population were separately reported (40 patients). The incidence rates (IR) were individually assessed for the outcomes of interest. The IR for atrial fibrillation/atrial flutter/atrial tachycardia ranged between 6.1 and 13.9 events/100 pts–year. The IR of atrial standstill ranged between 0 and 2 events/100 pts-year. The IR for malignant ventricular arrhythmias reached 10.2 events/100 pts–year and 15.6 events/100 pts–year for appropriate implantable cardioverter–defibrillator (ICD) interventions. The IR for advanced conduction disturbances ranged between 3.2 and 7.7 events/100 pts–year. The IR of thromboembolic events reached up to 8.9 events/100 pts–year. Our results strengthen the need for periodic cardiological evaluation focusing on the early recognition of atrial arrhythmias, and possibly for the choice of preventive strategies for thromboembolic events. The frequent need for cardiac pacing due to advanced conduction disturbances should be counterbalanced with the high risk of malignant ventricular arrhythmias that would justify ICD over pacemaker implantation.